2018
DOI: 10.3126/nepjoph.v10i2.20031
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Luxation of the Eye Ball with Optic Nerve Transection Following Road Traffic Accident: Report of Two Cases and Brief Review of Literature

Abstract: Background: Traumatic luxation of the eye ball is rare with only 106 cases reported in PubMed till date. The anatomic location of the eyeball within the socket and the resilience of the globe to pressure force, attachment to extraocular muscles and optic nerve prevents luxation during trauma. Case: Road traffic accidents (RTA) is the most common cause for these injuries and the outcome can vary from complete recovery on repositioning to visual loss due to globe perforation or optic nerve injury. We repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Song and Carter described abrupt deceleration as a cause of globe luxation. 6,7 In the present case series, case 1, the patient i.e. live donor had severe ocular injury that the eye was unsalvageable.…”
Section: Discussionmentioning
confidence: 69%
“…Song and Carter described abrupt deceleration as a cause of globe luxation. 6,7 In the present case series, case 1, the patient i.e. live donor had severe ocular injury that the eye was unsalvageable.…”
Section: Discussionmentioning
confidence: 69%
“…Many theories have been proposed like the hydraulic or buckling theory, medial penetration theory of Morris, orbital fractures reducing the orbital space, sudden deceleration force, sudden rise of intraocular pressure, and direct traction on the eye ball. 7,8 In a study by Amaral et al most cases of traumatic globe luxation could be found in patients who had suffered traffic accidents (52.9%), followed by falls (8.8%), hitting (5.9%), and assaults (5.9%). Other causes accounted for the remaining cases (26.5%).…”
Section: Discussionmentioning
confidence: 98%
“…In the ED, TGS may present following high energy motor vehicle accidents and can also be seen when someone grips the eyeballs during a ght, or secondary to birth trauma with compression of the cranium. [14][15][16][17][18][19][20][21][22] The pathogenesis of SGL is not fully elucidated. However, different pathological processes and risk factors have been reported.…”
Section: Discussionmentioning
confidence: 99%